2020
DOI: 10.3847/1538-4365/ab53e1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Kinks and Folds in the Solar Wind

Abstract: Parker Solar Probe (PSP) observations during its first encounter at 35.7 R have shown the presence of magnetic field lines which are strongly perturbed to the point that they produce local inversions of the radial magnetic field, known as switchbacks. Their counterparts in the solar wind velocity field are local enhancements in the radial speed, or jets, displaying (in all components) the velocity-magnetic field correlation typical of large amplitude Alfvén waves propagating away from the Sun. Switchbacks and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 31 publications
8
109
0
Order By: Relevance
“…Simple scaling arguments (assuming an inversion which convects outward at the background solar wind speed, while straightening out at the local Alfvén speed) indicate that non-eruptive loops should not be able to form inversions which survive out to 1 AU (Owens et al 2020). However, as above, the more detailed MHD modelling by Tenerani et al (2020) suggests that plasma effects may result in inversions surviving further into the heliosphere. Inversions which have been attributed to loop opening have been observed in streamer belt solar wind with PSP near perihelion, where the inversions are most likely to be intact (Rouillard et al 2020).…”
Section: Inverted Heliospheric Magnetic Fieldmentioning
confidence: 88%
See 1 more Smart Citation
“…Simple scaling arguments (assuming an inversion which convects outward at the background solar wind speed, while straightening out at the local Alfvén speed) indicate that non-eruptive loops should not be able to form inversions which survive out to 1 AU (Owens et al 2020). However, as above, the more detailed MHD modelling by Tenerani et al (2020) suggests that plasma effects may result in inversions surviving further into the heliosphere. Inversions which have been attributed to loop opening have been observed in streamer belt solar wind with PSP near perihelion, where the inversions are most likely to be intact (Rouillard et al 2020).…”
Section: Inverted Heliospheric Magnetic Fieldmentioning
confidence: 88%
“…Inversions of this type are less commonly observed at 1 AU, suggesting that they may straighten out, become damped, or otherwise merge into the background solar wind before reaching such distances. Modelling of these inversions by Tenerani et al (2020) has indeed indicated that an inverted magnetic structure, travelling outwards at the Alfvén speed, could reach distances accessible to PSP, but will tend to be removed from the field at greater heliocentric distances as a result of developing density and magnetic fluctuations.…”
Section: Inverted Heliospheric Magnetic Fieldmentioning
confidence: 99%
“…The study by Borovsky [12] suggests that switchbacks do not evolve after 0.3 AU, as if they had stopped interacting with the surrounding turbulent wavefield. Several studies suggest that switchbacks observed closer to the Sun by Parker Solar Probe do interact with the ambient magnetic field: Krasnoselskikh et al [33] argue that wave activity at the boundary of switchbacks may contribute to mixing and eventually to their weakening while Tenerani and et al [56], using simulations, conjecture that they originate in the lower corona and survive out to Parker Solar Probe distances. All these results support the idea that the concentration of switchbacks is higher at the perihelion of Parker Solar Probe than farther out.…”
Section: Discussionmentioning
confidence: 99%
“…4(a). These magnetic field reversals, also known as "switchbacks", have been observed to be pervasive in PSP's initial orbits, but their origin and physical nature remains a mystery Bale et al 2019;Tenerani et al 2020;de Wit et al 2020;Horbury et al 2020). Directly before this 30 minute-duration switchback, Fig.…”
Section: Event 2: April Foolsmentioning
confidence: 99%